The Lebanese Post-Civil War Novel - Lang, Felix. author. aut Link
XI, 263 p.
Keywords: After the Lebanese Civil War, many Lebanese novelists committed themselves to building a "memory for the future." What resulted was a vital contribution to the legacy of contemporary Arabic literature. Through interviews, literary analysis, and the lens of trauma studies, Lang sheds light on what it means to remember through post-war literature.